Assessment of Non-Computer Assessed Tests to Increase Professional Competence of School Counselors (Universitas Negeri Semarang, 2018)
The objectives of this study were (1) to describe and analyze non computer-assisted assessment (2) to produce a hypothetical model of computer-assisted non-test assays to improve the professional competence of School counselors and (3) to know the effectiveness of non computer-assisted assessment to improve the professional competence of School counselors. This research uses the Research and Development (R & D) method to develop computer-assisted non-test assays to improve the professional competence of school counselors. Assessment of non computer-assisted tests proved to be effective in improving the professional competence of school counselors especially on the aspects of mastering aspects and practical assessment to understand the condition, needs, and problems of learners. Discussion of the findings of this study focused on the application of non-test assessments in Junior High School Sukoharjo District.